Sub-structure Coupling for Dynamic Analysis : Application to Complex Simulation-Based Problems Involving Uncertainty /: Application to Complex Simulation-Based Problems Involving Uncertainty. (2019) - Jensen, Hector; Papadimitriou, Costas
No abstract available